Effects of dietary phytase supplementation on growth performance and apparent digestibility coefficients of Pacific White Shrimp Litopenaeus vannamei. (17th July 2016) - Qiu, X.; Davis, D.A.
Abstract: A growth trial and a digestibility trial were conducted to evaluate the efficacy of phytase supplemented to practical shrimp feeds. The 5 weeks growth trial evaluated the effects of phytase supplementation in replete phosphorus (P) diets on the performances and compositions of juvenile Pacific white shrimp, Litopenaeus vannamei . No significant differences were observed in final biomass, final mean weight, weight gain, feed conversion ratio (FCR), protein retention and survival across all the treatments. Shrimp reared on the P deficient diet had significantly higher P retention and lower whole body P levels as compared to shrimp fed the other diets. Copper content in the whole shrimp body was significantly increased in the treatment supplemented with 1, 000 IU kg −1 feed phytase. The digestibility trial was conducted to study the combined effects of phytase supplementation levels and diet type (plant‐based versus fishmeal‐based) on apparent digestibility coefficients of Pacific white shrimp, Litopenaeus vannamei . There were no effects of diet type so the data was combined. Phytase incorporation at both 500 and 2, 000 IU kg −1 significantly improved protein digestibility, whereas P digestibility was enhanced when 2, 000 IU kg −1 phytase was supplemented to the diet. Apparent digestibility coefficients of alanine, arginine, aspartic acid, cysteine, glutamic acid, glycine, histidine, isoleucine, leucine, lysine, methionine, ornithine, phenylalanine, proline, serine, threonine, tyrosine and valine were significantly increased when fed diets contained 500 and 2, 000 IU kg −1 phytase supplementation. Results of this work demonstrate that under the conditions of the study growth was not enhanced by phytase supplementation in P replete diets. However, nutrient retention for Cu and digestibility of P, protein and a number of amino acids were enhanced.